Opportunities and challenges of climate change adaptation across Europe: A case study analysis from the MACSUR knowledge hub - Roggero, P. P.; Bellocchi, G.; Bojar, W.; Cammarano, D.; Daalgard, T.; Dono, G.; Lehtonen, Heikki; Mula, L.; Øygarden, L.; Schönhart, M.; Seddaiu, G. (Italian Society of Agronomy, 2017)
Designing adaptive pathways to climate change in agriculture under uncertainty is a multidimensional, context-sensitive process with implications for researchers and stakeholders. We report the outcomes of a European case-study analysis across Europe conducted in the context of the MACSUR project. Crop, livestock and grassland and trade modelling, stakeholder engagement and co-researching with farmers were used differently by each research team depending on the available data or local skills. Adaptive responses ranged from changing sowing date to crop diversification or change farm structure. Despite the diversity of climates, methods and local contexts, many converging outcomes emerged, including the need for farmers to learn to perceive climate change, for policy makers to invest private-public partnerships and for researchers to identify adaptation options by investing on long-term experiments and on integrating education and communication in adaptation research.
Opportunita' e sfide dell'adattamento ai cambiamenti climatici in Europa: Analisi di casi studio dal progetto MACSUR knowledge hub
Keywords: adaptive capacity; integrated analyses; modelling; wicked issues; stakeholders